A MECHANISTIC MODEL ON METHANE OXIDATION IN A RICE RHIZOSPHERE - Van Bodegom P.; Goudriaan Ja.; Leffelaar P. (My University, 2001)
A mechanistic model is presented on the processes leading to methane oxidation in rice rhizosphere. The model is driven by oxygen release from a rice root into anaerobic rice soil. Oxygen is consumed by heterotrophic and methanotrophic respiration, described by double Monod kinetics, and by iron oxidation, described by a second order reaction. Substrates for these reactions - ferrous iron, acetate and methane - are produced by an exponential time dependent organic matter mineralisation in combination with modified Michaelis Menten kinetics for competition for acetate and hydrogen. Compounds diffuse between rhizosphere, root and atmosphere. A diffusion resistance between the rice root and shoot is included. Active transport across the root surface occurs for root exudation and plant nutrient uptake. Iron adsorption is described dependent on pH. The model predicts well root oxygen release, compound gradients and compound concentrations in a rice rhizosphere. Methane oxidation estimates are comparable to experimental estimates. A sensitivity analysis showed however that methane oxidation is highly dependent on model initialisation and parameterisation, which is highly dependent on the history of the rhizosphere and root growth dynamics. Equilibrium is not obtained within the period that a single root influences a soil microsite and results in a large change in methane storage. Equilibrium is moreover dependent upon the diffusion resistance across the root surface. These factors make methane oxidation dynamics highly variable in space and time and dependent on root dynamics. The increased understanding of methane oxidation does not directly lead to increased predictive abilities, given this high variability and the uncertainties involved in rhizosphere dynamics.
Keywords: DIFFUSION; HETEROTROPHIC RESPIRATION; IRON OXIDATION; METHANOGENESIS; METHANOTROPHY; REDUCTION; ROOT OXYGEN RELEASE